Nonlinear optical devices: Properties of polyaniline based conducting polymers - SHARMA, SUDHIR KUMAR (2003)
We report on the investigation of a series of polyaniline based conducting polymers with rather different backbone structure and energy gap in order to explore the effect of their molecular architecture on nonlinear optical properties. In particular, we report on the dispersion of x((3)) (-omega; omega, -omega, omega) in the spectral range covering the rising slope of the optical absorption as well as in off resonance conditions.